4-(2-Butyl-6,7-dichloro-2-cyclopentyl-indan-1-on-5-yl) oxobutyric acid inhibits angiogenesis via modulation of vascular endothelial growth factor receptor 2 signaling pathway - Zhou, Tianli; Li, Yunda; Zhang, Heqiang; Pan, Lei; Pang, Jinglong; Yuan, Qian; Li, Guiyang; Jie, Lingjun; Wang, Yan; Zhang, Yanhui (Frontiers in Cardiovascular Medicine, 2022)
4-(2-Butyl-6,7-dichloro-2-cyclopentyl-indan-1-on-5-yl) oxobutyric acid (DCPIB), was discovered to be a potent and specific antagonist of volume-regulated anion channel that is closely linked to angiogenesis. However, the effect of DCPIB on angiogenesis remains unclear. Here, we found that DCPIB inhibited angiogenesis in the corneal suture and myocardial infarction in vivo model. In addition, DCPIB inhibited human umbilical vein endothelial cell migration, tube formation and proliferation in vitro. Moreover, DCPIB repressed the activation and expression of vascular endothelial growth factor receptor 2 (VEGFR2) and its downstream signaling pathway. Computer modeling further confirmed that DCPIB binds with high affinity to VEGFR2. Collectively, we present evidence supporting an antiangiogenic role of DCPIB by targeting VEFGR2 signaling pathway, which suggests that DCPIB is a valuable lead compound for the treatment of angiogenesis-related diseases.